IDENTIFICATION AND SEQUENCING BY NMR SPECTROSCOPY OF THE CARBOHYDRATE MOIETY IN A SAPONIN FROM Barringtonia asiatica - Rymond J Rumampuk (Indonesian Journal of Chemistry, 2001)
A trisaccharide chain in a saponin from the seeds of Barringtonia asiatica has been identified and sequenced as {[b-D-galactopyranosyl(1®3)- b-D-glucopyranosyl(1®2)]-b-D-glucuronopyranosyloxy} using a combination of homonuclear and heteronuclear correlation NMR spectroscopy. The 1H and 13C NMR signals of the sugar residues can be determined and distinguished from one other by use of the HMQC-TOCSY technique. Anomeric configurations were unambiguously assigned from the vicinal coupling constants 3JH-1,H-2 of the anomeric protons. Inter-glycosidic linkage assignments were elucidated using  HMBC.